2015
DOI: 10.1007/s10943-015-0008-7
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to the Conceptualization and Measurement of Religiosity and Spirituality in Mental Health Research

Abstract: Investigating religiosity and spirituality may help to further elucidate how individuals' worldviews influence their attitudes, behavior, and overall well-being. However, inconsistencies in how these constructs are conceptualized and measured may undercut the potential value of religiosity and spirituality research. Results from a survey of undergraduate students suggest that laypeople define spirituality as independent from social influence and that few people associate religiosity with negative terms. A cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 29 publications
2
29
0
2
Order By: Relevance
“…Spirituality and religiosity are intricate constructs that describe peoples' fundamental beliefs about existence that form attitudes and behavior across many different cultures (Baumsteiger and Chenneville 2015). Generally, studies show that people with higher levels of spirituality and religiosity have lower levels of depression and anxiety, improved quality of life, a higher pain tolerance and a lower prevalence of chronic disease (Lucchetti et al 2013;Koenig 2009;Koenig 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Spirituality and religiosity are intricate constructs that describe peoples' fundamental beliefs about existence that form attitudes and behavior across many different cultures (Baumsteiger and Chenneville 2015). Generally, studies show that people with higher levels of spirituality and religiosity have lower levels of depression and anxiety, improved quality of life, a higher pain tolerance and a lower prevalence of chronic disease (Lucchetti et al 2013;Koenig 2009;Koenig 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Religiosity-"adherence to beliefs, doctrines, ethics, rituals, texts, traditions, and practices related to a higher power and associated with an organized group" (Baumsteiger & Chenneville, 2015, p. 2345)has been inversely associated with mental health indices in African American (AA) adolescents (see Mattis & Mattis, 2011). As research points to the psychologically beneficial role of religiosity, only a few studies have investigated the role of religion in mitigating depressive symptoms in the context of stress and adversity for AA adolescents (Grant et al, 2000;Greening & Stoppelbein, 2002;Molock et al, 2007).…”
mentioning
confidence: 99%
“…[13,14] The preponderance of evidence suggests that spiritual care of psychiatric patients matters and that both patients and providers benefit when spiritual needs are correctly assessed and implemented through proper interventions. [9,15,16] Foskett and Wilson-Rudd (2004) [14] have suggested that mental health caregivers and providers should be cognizant of patients' religious and spiritual beliefs, and they should seek to comprehend what functions they serve. Despite this knowledge, spirituality has been shown to be a frequently neglected focus of psychiatric consideration and intervention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite this knowledge, spirituality has been shown to be a frequently neglected focus of psychiatric consideration and intervention. [4,11,13,15,16] …”
Section: Literature Reviewmentioning
confidence: 99%